Acute treatment of duodenal ulcer: a multicentre study to compare ranitidine 150 mg twice daily with ranitidine 300 mg once at night. Issue 9 (September 1986) - Lee, F I; Reed, P I; Crowe, J P; McIsaac, R L; Wood, J R
Abstract : A randomised double blind clinical trial was undertaken in the UK and Ireland to compare ranitidine 300 mg given as a single bed time tablet with ranitidine 150 mg twice daily in the acute treatment of duodenal ulcers. Of the 594 patients with endoscopically diagnosed duodenal ulcer entered into the trial, 424 patients had complete endoscopic findings on which healing rates at four weeks were determined. By this time 156 of 201 (78%) patients healed with ranitidine 300 mg nocte compared with 186 of 223 (83%) receiving ranitidine 150 mg twice daily (p = 0.28). After eight weeks of treatment 97% of the patients in each group were healed. The healing rates for smokers and non-smokers did not differ significantly at either four or eight weeks. Each regimen was equally effective in reducing day and night-time pain. Adverse events were reported in 23 patients overall; 12 were withdrawn from the trial. Minor abnormalities in liver function tests were noted in three patients. The trial confirmed that a single dose of ranitidine 300 mg given at night is a safe, effective alternative treatment to ranitidine 150 mg bd for the acute treatment of duodenal ulcer.